NUTRITIONAL STUDIES ON THE YEAST PHASE OF BLASTOMYCES DERMATITIDIS AND B. BRASILIENSIS - Gilardi, Gerald L. (1962)
Gilardi, Gerald L. (University of Maryland, College Park) and Norman C. Laffer. Nutritional studies on the yeast phase of Blastomyces dermatitidis and B. brasiliensis. J. Bacteriol. 83:219–227. 1962.—Nutritional characteristics of the yeast phase of 22 cultures of the genus Blastomyces (9 of B. brasiliensis and 13 of B. dermatitidis) were examined to see if differences in nutritional behavior occurred which could serve as an aid in a more definitive classification. The studies included vitamin and amino acid requirements, carbon and nitrogen assimilation tests, and comparison of growth obtained with quiescent, agar slant, and shake cultures. Both species synthesized their own vitamins, utilized the same 21 carbon and 25 nitrogen substrates as the sole source of the respective element, and produced their most luxuriant growth in shake cultures in the presence of either ammonium salts or organic nitrogen. Sulfur-containing compounds, reducing agents, and Tween 80 were observed to retard or inhibit growth. Inhibition of yeast phase maintenance, and the conversion to the mold phase at 35 C, occurred in the presence of tyrosine. No difference was detected between the two species; variation occurred only at the culture level. On the basis of the similarity of nutritional characteristics, there appears to be no justification to separate the two species into separate genera, as proposed by some authors.